Novel Antifungal Peptides Produced by Leuconostoc mesenteroides DU15 Effectively Inhibit Growth of Aspergillus niger - Muhialdin B.J.; Hassan Z.; Abu Bakar F.; Algboory H.L.; Saari N. (Blackwell Publishing Inc., 2024)
The ability of Leuconostoc mesenteroides DU15 to produce antifungal peptides that inhibit growth of Aspergillus niger was evaluated under optimum growth conditions of 30 °C for 48 h. The cell-free supernatant showed inhibitory activity against A. niger. Five novel peptides were isolated with the sequences GPFPL, YVPLF, LLHGVPLP, GPFPLEMTLGPT, and TVYPFPGPL as identified by de novo sequencing using PEAKS 6 software. Peptide LLHGVPLP was the only positively charged (cationic peptides) and peptide GPFPLEMTLGPT negatively charged (anionic), whereas the rest are neutral. The identified peptides had high hydrophobicity ratio and low molecular weights with amino acids sequences ranging from 5 to 12 residues. The mode of action of these peptides is observed under the scanning electron microscope and is due to cell lysis of fungi. This work reveals the potential of peptides from L. mesenteroides DU15 as natural antifungal preservatives in inhibiting the growth of A. niger that is implicated to the spoilage during storage.